Your Farm as a Water Storage System: Steps to Establish an Agreement with the Water Management Districts - Brandon Quinn-Ivey; Sandra M. Guzman (EDIS)
This publication introduces water storage strategies known as Dispersed Water Management (DWM) and Water Farms (WF) and describes the process that a private landowner should follow to obtain a permit and begin a water storage agreement with the South Florida Water Management District (SFWMD) and the St. Johns River Water Management District (SJRWMD). Written by Brandon Quinn-Ivey and Sandra M. Guzmán, and published by the UF/IFAS Department of Agricultural and Biological Engineering, September 2022.